Occurrence and Detection of Killer Yeasts on Chenin Blanc Grapes and Grape Skins - Jacobs, C.J.; Fourie, I.; van Vuuren, H.J .J. (South African Journal of Enology and Viticulture, 2017)
Two hundred and thirty killer yeast strains were selectively isolated from Chenin blanc grapes and grape skins collected from six wineries. The killer yeasts were divided into nine groups based on their colony morphology and colour on modified Wallerstein laboratory nutrient agar. All strains fermented Chenin blanc grape must (pH 3,5; 40 mg/ I free SO, and 5% (v/v) ethanol) at l4°C. Existing techniques in which methylene blue are used were evaluated to detect killer yeasts, to determine interactions between different killer phenotypes, and to determine the sensitivity of commercial strains to the killer toxins.